Epidermal or dermal collagen VII is sufficient for skin integrity: insights to anchoring fibril homeostasis - Conradt, Gregor; Haußer-Siller, Ingrid; Nyström, Alexander (The journal of investigative dermatology, 2024)
Collagen VII forms anchoring fibrils that are essential for the stability of the skin and other epithelial organs. In addition to such structural functions, it is emerging that collagen VII fills instructive functions. Collagen VII is synthesized by both epithelial cells and fibroblasts. Genetic loss of collagen VII causes dystrophic epidermolysis bullosa, which manifests with chronic skin fragility and fibrosis. Significant progress has been made in developing therapies for dystrophic epidermolysis bullosa; however, such work has also raised questions on the importance of the cellular source of collagen VII for maintenance of tissue integrity and homeostasis. Toward this end, we engineered mice that kept the physiological expression of collagen VII only in epithelial cells or in fibroblasts. Our study revealed that production of collagen VII either by keratinocytes or fibroblasts alone is sufficient for creation of mechanically robust skin. Importantly, we also show tissue-diverse dependence on epithelial and mesenchymal production of collagen VII and provide support for limited amounts of collagen VII being sufficient for tissue protection. Furthermore, a disconnect between collagen VII abundance and anchoring fibril numbers supports the concept that restoration of fully physiological collagen VII levels may not be needed to achieve complete mechanical protection of dystrophic epidermolysis bullosa skin.